The Compromises of Printing Organic Electronics: A Case Study of Gravure‐Printed Light‐Emitting Electrochemical Cells. (26th February 2014) - Hernandez‐Sosa, Gerardo; Tekoglu, Serpil; Stolz, Sebastian; Eckstein, Ralph; Teusch, Claudia; Trapp, Jannik; Lemmer, Uli; Hamburger, Manuel; Mechau, Norman
<x xml:space="preserve">Abstract</x> Light‐emitting electrochemical cells (LECs) are fabricated by gravure printing. The compromise between device performance and printing quality is correlated to the ink formulation and the printing process. It is shown that the rheological properties of the ink formulations of LECs can be tailored without changing the chemical composition of the material blend. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>